Educational Nursing Interventions in Post-COVID-19 Heart Transplantation: An Experience Report - Soares, Vivian Lavor; Poltroniéri, Nadja Van Geen; Kobayashi , Rika Miyahara; Gaspar , Adrielly Raimundo; Simonetti, Sérgio Henrique (Brazilian Journal of Transplantation, 2022)
Introduction: COVID-19 infection can lead to fulminant myocarditis, making the pretransplant process shorter and more rapidly progressing. Objective: To report the case of a patient who after COVID-19 infection evolved to heart transplantation, as well as the educational nursing interventions performed in this process. Methods: This is a case report approved by the Research Ethics Committee, under protocol no. 52318721.7.0000. 5462, described according to the CARE guidelines, and a systematization of nursing care for an adult who, upon contracting COVID-19 in June 2020, evolved within six months to myocarditis, heart failure, and transplantation, in a cardiology hospital in the city of São Paulo (SP). Results: A young male adult presented with mild symptoms of COVID-19 and progressed with worsening systemic symptoms, failure to withdraw vasoactive drugs, and implantation of an intra-aortic balloon device with outcome to heart transplantation. The reported case showed the evolution of this young patient, with no history of cardiovascular disease, evolving to heart transplantation, differently from what is reported in the literature about transplant patients who acquired COVID-19. The evolution of the disease required systematized nursing care and educational interventions, the focus of this study to obtain health education outcomes. Conclusion: The patient, with a nursing diagnosis of improved knowledge disposition, through the intervention of improved health education, obtained knowledge of heart failure control and had heart transplantation as the outcome, with in-hospital adherence to therapy, and should be monitored after discharge.